Strategy on Cotton Varietal Improvement Facing Global Climate Change - EMY SULISTYOWATI (Perspektif, 2011)
Global climate change has been a serious challenge to agriculture in future due to its influence on natural genetic diversity and ecosystem.  The phenomenon of global climate change has to be faced by the world, and therefore organized preparation of adaptation, anticipation, and mitigation scenarios has to be set up.  Cotton is very susceptible to climate change, because climatic factors affect cotton growth and yield.  Adaptation to drought can be approached by selecting early maturing cotton varieties.   Anticipation scenario for facing the effect of global climate change is done by developing new cotton varieties tolerant to drought,  excessive rain, and CO2 concentration in the air.  Two high yielding varieties, Kanesia 14 and Kanesia 15, have been released to anticipate the drought stress.  To anticipate lengthy rainy season, the cotton breeding has obtained promising okra-leave cotton lines.   Moreover, anticipation of excessive CO2 concentration in the air will be approached by engineering transgenic cotton varieties expressing efficient photosynthetic genes of C3 plants. Mitigation of climate change will be met by developing new cotton varieties tolerant to salinity, because global climate change will increase saline areas.   Keywords : Climate change, varieties development, adaptation, anticipation, mitigation